Increasing the Power of the Test Through Pre-Test – A Robust Method - Yunus, Rossita Mohamad; Khan, Shahjahan (Taylor & Francis, 2011)
Robust test procedures are developed for testing the intercept of a simple regression model when the slope is (i) completely unspecified, (ii) specified to a fixed value, or (iii) suspected to be a fixed value. Defining (i) unrestricted (UT), (ii) restricted (RT), and (iii) pre-test test (PTT) functions for the intercept parameter under the three choices of the slope, tests are formulated using the M-estimation methodology. The asymptotic distributions of the test statistics and their asymptotic power functions are derived. The analytical and graphical comparisons of the tests reveal that the PTT achieves a reasonable dominance over the other tests. Copyright © Taylor & Francis Group, LLC.